VEGETATIVE CORRELATES OF COGNITIVE PROCESSES IN STRESS SITUATION - Bakhchina, Anastasya V.; Polevaya, Sophya A.; Parin, Sergey B. (European Scientific Journal, ESJ, 2014)
In this series of experiments we investigated the relationship between the structure of the behavioral activity of a person in a virtual computer environment, and the structure of physiological reactions in the context of legitimate and random dynamics of informative images. In the experiments was implemented the technology of integrated monitoring of the functional state and event of context in conditions of a natural human activity in a virtual computer environment. AIM: To study of autonomous components of a functional system, providing purposeful behavior of the person in stress information contexts. METHODS: Sixty healthy subjects and fifty addicted patients (age or gender difference is not taken into account) participated in the study. Heart rate measurement was performed with the help of the system of the telemetry wireless registration of the heart rhythm. During the experiment we recorded face of the subject and the content of his computer screen. CONCLUSION: The operational management of heart rhythm is agreed with the level of uncertainty of information image.